Relationship Marketing Strategy in Building Customer Loyalty for Local Decapterus SPP (Muroaji) Products - Citra Elya Lestari; Muhammad Musyfiq Salami (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2026)
This study analyzes the implementation of relationship marketing strategies in building customer loyalty for Local Decapterus SPP (Muroaji) products at PT Satya Trinadi Komira Perkasa. This research uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving informants consisting of directors, managers, and marketing staff. Data analysis was conducted using a descriptive method, and validity was tested using triangulation techniques. The results show that the relationship marketing strategy implemented by PT Satya Trinadi Komira Perkasa has been running well and plays an important role in increasing customer loyalty. This is reflected in consistent product quality, open and responsive communication, and fast and responsible complaint handling. However, the company still faces constraints in the form of dependence on fishing seasons and supply limitations. Therefore, the company needs to continuously evaluate and strengthen its strategies to maintain long-term relationships with customers.